Halal Certification: The Role of Religiosity and Consumer Pressure on MSMEs' Intention to Register Halal Certification in East Java - Nurul Islami, Novita (El-Qish: Journal of Islamic Economics, 2023)
The potential for superior products owned by Indonesia is enormous, especially those produced by Micro, Small, and Medium Enterprises (MSMEs). One of the efforts that can be made to increase the competitiveness of MSMEs products is halal certification. This study aims to determine the perspective of the role of religiosity and consumer pressure on MSMEs' intentions in Jember Regency in registering their products in halal certification. This research is a qualitative descriptive study with MSMEs research subjects in East Java. Retrieval of data using interview techniques, observation, questionnaire, and documentation. Findings. Based on the results and discussion, it can be concluded that religiosity and consumer pressure have a role in the intention of MSMEs to register their products in the halal certification program. However, it was found that consumer pressure as an external factor has a more substantial role than religiosity as an internal factor. Based on the conclusions, this study recommends suggestions to encourage MSMEs in East Java to have high intentions in registering their products in halal certification. It is necessary to have an optimal role from various parties, including the government (for example, the Office of Cooperatives and MSMEs, the Office of Industry and Trade, and Local Government), Stakeholders, Banking, and communities or forums to provide training, mentoring and providing access to MSMEs mainly related to halal certification and increasing the capacity of product competitiveness.